A Review of Family Caregiver’s Responses of Care to Patients Undergoing Hemodialysis - Faridah, Virgianti Nur; Lestari, Trijati Puspita; Qowi, Nurul Hikmatul (Poltekita : Jurnal Ilmu Kesehatan, 2024)
The limitations of CKD patients require families to care for family members who suffer from CKD. This research analyzes family experiences in caring for family members with CKD. This research method uses a descriptive design with a scoping review approach. Article searches used four journal databases: PubMed, ScienceDirect, EBSCO, and Google Scholar. Articles that met the inclusion criteria, including a publication range from 2015 to 2022 in English and Indonesian and free access to the full-text PDF, were evaluated before selection. The research results based on a review of 10 articles show that family members have different responses in caring for CKD sufferers. Acceptance of known kidney disease indicates coping with solid efforts. The family will also continue to fight to get the best treatment for the patient's recovery. Apart from that, the family and the patient can make decisions regarding the continuation of the patient's therapy program. Families need emotional support from the surrounding environment. Psychological responses will increase along with the lack of family acceptance of the condition of the patient being treated.